SISTEM PENDUKUNG KEPUTUSAN KARYAWAN TERBAIK MENGGUNAKAN METODE PROFILE MATCHING DI PT PRESTASI RETAIL INNOVATION - Heykal Fauzan; Akbar Muchbarak; Ari Irawan (Jurnal Ilmu Komputer dan Sistem Informasi, 2026)
The assessment of the best employees at PT Prestasi Retail Innovation has traditionally been conducted manually, which is considered inefficient and tends to be subjective. This study aims to design and develop a Decision Support System (DSS) based on Java using the Profile Matching method as a solution to enhance objectivity, efficiency, and transparency in the employee selection process. The system applies evaluation criteria and sub-criteria determined by the company, such as discipline, creativity, work ethic, attendance, and performance. The research methods include observation, documentation, and interviews to identify system requirements and assessment parameters. The system is developed using an object-oriented approach with the support of Unified Modeling Language (UML), implemented with the Java programming language, and integrated with a MySQL database. The Profile Matching method is applied through GAP analysis between employees’ actual profiles and the ideal profile, which is then processed into employee rankings. The results show that the system successfully automates the evaluation process, generates more objective recommendations, and supports decision-making related to promotions, rewards, and performance evaluation. The application of a DSS based on the Profile Matching method has proven to provide real benefits for management in human resource management.